Bessere Daten für die Wirtschafts- und Sozialforschung - eine Erwiderung - Moritz Drechsel-Grau; Andreas Peichl; Kai Daniel Schmid (Wirtschaftsdienst, 2015)
Unsere Anregung des Vergleichs der Ungleichheitsentwicklungen anhand verschiedener Teilpopulationen zielt nicht darauf, die Datenqualität des SOEP anhand "scheinbar widersprüchlicher" Befunde infrage zu stellen. Vielmehr geht es darum, den Mehrwert komplementärer Betrachtungen und Teilergebnisse zu nutzen und die Grundlagen hierfür einzufordern. Aus diesem Grund plädieren wir für eine systematische Verknüpfung aller amtlich erhobenen Daten (Prozess- und Befragungsdaten) für wissenschaftliche Zwecke, wie es in vielen anderen Ländern üblich ist, um den Wissenschaftsstandort Deutschland zu stärken. – – Jan Goebel and Carsten Schröder reply to the proposal of Andreas Peichl et al. to combine the Taxpayer Panel with the German Socio-economic Panel. They concede that both measures help to understand the development of income distribution. But problems may occur because the different concepts are only partially congruent. Peichl et al. also think that complementary analyses of survey data and administrative data offer a better understanding of the evolution of income distribution in Germany, as these provide different information. They argue that mutual cross-checking of both kinds of data as well as plausibility considerations in the macroeconomic context can partly offset imperfect congruency when assessing inequality trends. Linking both kinds of data will further reduce uncertainty about the evolution of income distribution and improve research conditions and policy advice in Germany.
Keywords: D31; D33; 330